Going Down Memory Lane in the Application of Ajzen's Theory of Planned Behaviour Model to Measure Entrepreneurial Intention: An Sem-Pls Approach - Kwaku Amofah; Ramon Saladrigues (International Review of Management and Marketing, 2020)
Undoubtedly, technical education is the backbone of every nation's growth and development. Understanding and predicting business creation initiatives demand empirical studies using theory-oriented models that appropriately mirror the multi-faceted perception-based processes underlying entrepreneurial intentional and behaviour. Drawing on a model adapted from a study by Linan and Chen (2009), and based on the Theory of Planned Behaviour (TPB) by Ajzen, this article empirically investigates the influence of Perceived Behavioural Control, Subjective Norm and Attitude towards Entrepreneurship, on Entrepreneurial Intention using Structural Equation Modelling (SEM) – Smart Partial Least Square (PLS) approach. In addition, several hypotheses (demographic-oriented variables) in relation to TPB are investigated. Data were collected on 574 students from a public technical university in Ghana. The findings suggest that TPB is an important tool for predicting entrepreneurial intentions. Thus, the findings support the TPB for EI in Ghana. Two motivational factors (Attitude towards Entrepreneurship and Planned Behavioural Control) related to EI, but SN showed a non-significant association with EI. This study also found SN positively affecting attitude toward entrepreneurship and perceived behavioural control. However, only one (PSE-SN relationship) of the demographic-based hypotheses was significant. This study, however, cautions against the generalizability of the findings as the sample size comprises of students from a single institution. One of the theoretical implications of our study relates to evidence of the consistency of the theory of planned behavior in explaining entrepreneurial intention in the Ghanaian context. Future studies could replicate this research by sampling more technical universities in Ghana and other settings.